2003
DOI: 10.1103/physreve.68.067202
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude death induced by dynamic coupling

Abstract: The present paper shows that dynamic coupling induces amplitude death in coupled identical oscillators. For a simple limit-cycle oscillator, our theoretical analysis provides the necessary and sufficient condition for amplitude death. Furthermore, we guarantee that amplitude death never occurs, if each oscillator satisfies the odd number property that is known in the field of delayed-feedback control of chaos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(84 citation statements)
references
References 18 publications
0
83
1
Order By: Relevance
“…Konishi [14] has proposed another type of interaction which, in contrast to the cases discussed above has an evolving or "dynamic" coupling. Consider the Landau-Stuart systeṁ [14].ẏ…”
Section: Dynamic Couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Konishi [14] has proposed another type of interaction which, in contrast to the cases discussed above has an evolving or "dynamic" coupling. Consider the Landau-Stuart systeṁ [14].ẏ…”
Section: Dynamic Couplingmentioning
confidence: 99%
“…Konishi and coworkers [14,37,73,74] have studied a number of models with different types of connections, on networks of varying topologies. Analytical estimation of regimes of amplitude death have been carried out, and their analysis shows that the odd-number property that is known in delayed feedback control also exits in global dynamically coupled oscillators.…”
Section: Amplitude Death On Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently reported that amplitude death in two coupled identical oscillators can be induced by incorporating a dynamic coupling without a time delay [Konishi, 2003b;Konishi, 2004b]. These reports provided the following results: the death was observed in both numerical simulations and electronic circuit experiments [Konishi, 2003b;Konishi, 2004b]; a sufficient condition under which death never occurs was derived [Konishi, 2003b]; and a necessary and sufficient condition for death in van der Pol oscillators was obtained [Konishi, 2004b].…”
Section: Introductionmentioning
confidence: 70%
“…After then several works have been reported showing such transition in different coupled system like; mean field diffusive (MFD) coupled system [14], [15], time-delayed system [16], dynamic coupled system [17], conjugate coupled system [18], [19], diffusive and repulsive coupled system [20], [21] etc.…”
Section: Introductionmentioning
confidence: 99%